2005
DOI: 10.1161/01.hyp.0000172755.25382.fc
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor-α Activation Reduces Salt-Dependent Hypertension During Chronic Endothelin B Receptor Blockade

Abstract: Abstract-Endothelin B (ET B ) receptor stimulation inhibits sodium transport in a similar fashion as 20-HETE. Clofibrate, a peroxisome proliferator-activated receptor-␣ (PPAR-␣) agonist, increases protein expression of cytochrome P450 4A (CYP4A), which is responsible for 20-HETE synthesis in the kidney. Experiments were designed to determine whether clofibrate reduces hypertension associated with chronic ET B receptor blockade. Male Sprague-Dawley rats received either normal-salt (0.8% NaCl) or high-salt (8% N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…17 The exact role of PPAR-␣ in the regulation of blood pressure remains unclear, because several other studies conducted in various rat models of hypertension have provided inconsistent results. 18,19 It is currently not known whether renin activation associated with PPAR-␣ activation is a direct transcriptional effect of PPAR-␣ or if it should be regarded as a secondary phenomenon, attributable to concomitant blood pressure reduction or other ancillary effects of PPAR agonists (eg, antiinflammatory and antiproliferative effects on the vasculature or increased sympathetic activity).…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%
“…17 The exact role of PPAR-␣ in the regulation of blood pressure remains unclear, because several other studies conducted in various rat models of hypertension have provided inconsistent results. 18,19 It is currently not known whether renin activation associated with PPAR-␣ activation is a direct transcriptional effect of PPAR-␣ or if it should be regarded as a secondary phenomenon, attributable to concomitant blood pressure reduction or other ancillary effects of PPAR agonists (eg, antiinflammatory and antiproliferative effects on the vasculature or increased sympathetic activity).…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%
“…However, other PPAR-␣ agonists (ie, docosahexaenoic acid and clofibrate) have decreased BP in other models of hypertension, possibly by inhibiting NADPH oxidase-induced oxidative stress and inflammation in the vascular wall 29 and reducing endothelin-B receptor blockade in the kidney. 30 We previously showed that aldosterone increases myocyte MMP activity and extracellular signal-regulated kinase phosphorylation 11 and may be inhibited by fenofibrate. 19 Similar to other in vivo models of HF (ie, mice subjected to pressure overload or angiotensin II infusions), aldosterone administration induces a proinflammatory and a profibrotic phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have indicated that increasing the renal formation of 20-HETE and/or EETs protects against the development of hypertension-induced proteinuria and glomerular disease (7,14,20,25,27,28) and that exogenous administration of 20-HETE opposes the effects of TGF-␤ and puromycin to increase P alb (4,12). The present results now extend these findings and indicate that glomeruli normally produce 20-HETE, EETs, diHETEs, and other HETEs and that the endogenous formation of both 20-HETE and EETs plays an essential role in the maintenance of the glomerular permeability barrier to albumin.…”
Section: Perspectivesmentioning
confidence: 99%